The Uncertainty in Physical Measurements An Introduction to Data Analysis in the Physics Laboratory - Fornasini, Paolo (Springer New York : Imprint: Springer, 2008)
All measurements of physical quantities are affected by uncertainty. Understanding the origin of uncertainty, evaluating its extent and suitably taking it into account in data analysis is essential for assessing the degree of accuracy of phenomenological relationships and physical laws in both scientific research and technological applications. The Uncertainty in Physical Measurements: An Introduction to Data Analysis in the Physics Laboratory presents an introduction to uncertainty and to some of the most common procedures of data analysis. This book will serve the reader well by filling the gap between tutorial textbooks and highly specialized monographs. The book is divided into three parts. The first part is a phenomenological introduction to measurement and uncertainty: properties of instruments, different causes and corresponding expressions of uncertainty, histograms and distributions, and unified expression of uncertainty. The second part contains an introduction to probability theory, random variable distributions and basic statistical tools. The third part introduces the readers to some basic data analysis procedures: propagation of uncertainty, least squares fit, chi square test, and confidence intervals to name a few. The introduction of probability and statistical tools is made on phenomenological grounds, as a natural response to the problems arising in the laboratory practice. The author has made a concentrated effort to guarantee both accuracy and clarity through the introduction of a large number of figures and worked examples, many of them taken from laboratory experimentations and practice. The book is enriched by the detailed proposal of several simple experiments. Paolo Fornasini is a Professor of Physics at the University of Trento, Italy. He is the author, with Giuseppe Dalba, of Esercizi di Fisica: Meccanica e Termodinamica (Springer 2006).<.